Reliability of anthropometric measurements in European preschool children: the ToyBox‐study. (August 2014) - De Miguel‐Etayo, P.; Mesana, M. I.; Cardon, G.; De Bourdeaudhuij, I.; Góźdź, M.; Socha, P.; Lateva, M.; Iotova, V.; Koletzko, B. V.; Duvinage, K.; Androutsos, O.; Manios, Y.; et al.
Summary: The ToyBox‐study aims to develop and test an innovative and evidence‐based obesity prevention programme for preschoolers in six European countries: Belgium, Bulgaria, Germany, Greece, Poland and Spain. In multicentre studies, anthropometric measurements using standardized procedures that minimize errors in the data collection are essential to maximize reliability of measurements. The aim of this paper is to describe the standardization process and reliability (intra‐ and inter‐observer) of height, weight and waist circumference (WC) measurements in preschoolers. All technical procedures and devices were standardized and centralized training was given to the fieldworkers. At least seven children per country participated in the intra‐ and inter‐observer reliability testing. Intra‐observer technical error ranged from 0.00 to 0.03 kg for weight and from 0.07 to 0.20 cm for height, with the overall reliability being above 99%. A second training was organized for WC due to low reliability observed in the first training. Intra‐observer technical error for WC ranged from 0.12 to 0.71 cm during the first training and from 0.05 to 1.11 cm during the second training, and reliability above 92% was achieved. Epidemiological surveys need standardized procedures and training of researchers to reduce measurement error. In the ToyBox‐study, very good intra‐ and‐inter‐observer agreement was achieved for all anthropometric measurements performed.